Insights into the role of complement regulatory proteins in HPV mediated cervical carcinogenesis. (November 2022) - Khan, Asiya; Das, Bhudev C.; Abiha, Umme; Sisodiya, Sandeep; Chikara, Atul; Nazir, Sheeraz Un; Das, Ankan M.; Rodrigues, Alexandre Gomes; Passari, Ajit Kumar; Tanwar, Pranay; Hussain, Showket; Rashid, Sabia; et al.
Abstract: The persistent infection of high-risk Human papillomavirus (HR-HPV) induced cervical cancer remains a challenge in women worldwide including India. Recent advances in cancer research have paved the way for advanced cancer treatment modalities including immunotherapy by manipulating the function or number of cytotoxic T cells. It is well established that anaphylatoxins like C3a and C5a of complement system influence tumor growth by evading apoptosis leading to progression of cancer. The role of the complement system, particularly the complement regulatory proteins (CRPs) which are important determinants of immune response play a crucial role in carcinogenesis. In a tumor microenvironment (TME) assisted suppression of immune effector cells may be achieved through CRPs. However, recent advances in pharmacogenomics including drug designing and combination of these approaches have provided a holistic understanding of signaling pathways and their crosstalk, to regulate cellular communications.This review describes the role of complement system; particularly CRPs in HPV induced cervical carcinogenesis which may be used for designing anti- HPV or cervical cancer therapeutics.